Hardware implementation of a FPGA-based universal link for LVDS communications - Sanchez, Luis (2015)
We present the first hardware implementation for a FPGA-based universal link for the transmission of different low-voltage differential signaling (LVDS) connections through a single LVDS connection between different devices. The main objective of this work is to reduce the number of wires in a network, for example in some satellites, with several groups of devices, to a single LVDS connection. This paper proposes a new communication protocol for successfully coding and decoding the data sent through the single connection. We propose a solution for one of the difficulties of LVDS standard due to the amount of wires needed for a duplex connection, significantly reducing the amount of wires required for a large network. The proposed solution has been implemented in an Atlys board with a Spartan 6 FPGA showing promising results.